Analisis Kebutuhan Model Penilaian Menulis Berbasis STEM untuk Meningkatkan Keterampilan Berpikir Kritis Mahasiswa - Sukenti, Desi; Tambak , Syahraini; Fabria, Rhani; Siregar, Ehdatul Puadi; Shomary, Sudirman (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2026)
21st-century learning demands that universities produce human resources capable of critical, creative, and adaptive thinking in response to developments in science and technology. One important skill that needs to be developed in Indonesian language learning is critical thinking skills through academic writing activities. This study aims to analyze the need to develop a STEM (Science, Technology, Engineering, and Mathematics)-based writing assessment model to improve students' critical thinking skills. The type of research used is survey research with a descriptive qualitative and quantitative approach. The research instruments include interview guidelines, needs analysis questionnaires, learning observation sheets, and documentation. The study involved six Indonesian language lecturers and 68 students consisting of 40 female students and 28 male students. The results show that the writing assessment process applied is still conventional and focuses more on linguistic aspects than students' critical thinking skills. This condition is reflected in the average achievement of students' overall critical thinking skills which only reached (65.1%), which indicates that the critical thinking aspect has not become the main focus in the writing assessment process. The needs analysis results indicate that lecturers and students require a writing assessment model that not only evaluates linguistic aspects but also integrates STEM components and critical thinking skill indicators as a basis for more authentic, objective, and comprehensive assessments. The desired assessment model includes a critical thinking indicator-based assessment rubric, the use of real-world problem contexts, the use of technology in the assessment process, and a feedback mechanism that supports the development of students' academic writing and critical thinking skills.